Bystanders’ reactions to animal abuse in relation to psychopathy, empathy with people and empathy with nature - Martín, Ana M.; Vera, Andrea; Marrero, Rosario J.; Hernández, Bernardo (Frontiers in Psychology, 2023)
Social and academic interest in animal abuse has recently increased thanks to greater awareness of the importance of biodiversity in promoting sustainability. The redefinition of human-animal relationships, in the context of the fight against speciesism and the defense of veganism, has also contributed to this greater attention. Moreover, public awareness of animal rights has strengthened social reactions to violence against animals, though there are still some social sectors that are indifferent to these changes. Thus, better knowledge of the psychological mechanisms underlying reactions to animal abuse could contribute to better informal social control of such abuse. The main aim of this study is to analyze the relationships between psychopathy, empathy with people and empathy with nature, and people's reactions to the abuse of protected and domestic animals, and to illegal dumping. Also, as previous studies have shown differences between men and women, both in animal abuse and in personality traits, gender is taken into account when analyzing these relationships. A total of 409 people, resident in a highly environmentally protected territory, participated in this study. They were between 18 and 82 years old and 49.9% women. Participants were asked about assigned punishments, as well as the probability of intervening personally and calling the police, in relation to ten scenarios, based on press releases, describing one of three types of transgression of environmental laws: abuse of protected animals, abuse of domestic animals or illegal dumping. They also responded to Spanish adaptations of the Inventory of Callous Unemotional Traits, the Basic Empathy Scale, the Dispositional Empathy with Nature Scale, and the Social Desirability Scale. Each participant was randomly given ten scenarios corresponding to just one transgression type but all the personality scales. Results show that people's reactions were greater for abuse of domestic than protected animals or for illegal dumping, irrespective of gender. Empathy with nature was related to the reaction against animal abuse more than empathy with people and psychopathy. Results are discussed highlighting the need for future research into similarities and differences between animal abuse and other types of environmental offences, which have many victims but no single being suffering.